HIRADC Analysis for Occupational Accident Prevention During 50K STG Major Overhaul Maintenance at PT. PLN Batam - Annisa Nur Hidayah; Hery Irwan (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
The electricity sector is categorized as a high-risk industry (asset-sensitive enterprise). At PT PLN Batam, particularly at the 124.5 MW Tanjung Uncang Combined Cycle Power Plant (PLTGU), the reliability of the Steam Turbine Generator (STG) system depends on routine large-scale maintenance, including the 50K Major Overhaul, which involves significant hazards such as high-voltage electricity, high pressure, extreme temperatures, and mechanical risks. This study aimed to analyze potential hazards, assess occupational risk levels, and determine appropriate control measures for the 50K Major Overhaul of the Steam Turbine Generator using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method. A qualitative descriptive approach was employed through field observations, interviews, and document analysis. The results identified 11 maintenance activities, consisting of 6 High Risk and 5 Medium Risk activities before control implementation. The highest risk was associated with working at heights, high-pressure and high-temperature systems, high-voltage electrical work, and the use of power tools, with a maximum Severity value of 5. After implementing engineering controls, administrative controls, competency requirements for certified personnel, and the use of personal protective equipment (PPE), all 11 activities were successfully reduced to the Low Risk category, with the Likelihood value decreasing to 1. These findings demonstrate that the systematic implementation of the HIRADC method effectively reduces occupational risks and provides a practical framework for improving safety performance during major overhaul activities at combined-cycle power plants.